NAVIGATING MULTILINGUAL ECOLOGIES: A CASE STUDY OF PRIMARY ESL TEACHERS’ PERSPECTIVES ON TRANSLINGUALISM IN SARAWAK - Irham, Nurul Anissma Nasuha; Zakaria, Nur Yasmin Khairani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study investigates the pedagogical beliefs and practices of primary English as a Second Language (ESL) teachers in Sarawak, Malaysia, which is a region defined by a complex multilingual ecology where English is frequently a third or fourth language (L3/L4). While the national English Language Education Reform: Roadmap 2015–2025 emphasizes monolingual, English-only instruction, this research explores how teachers navigate the disconnect between policy mandates and classroom realities. Drawing on Sociocultural Theory and Translanguaging, the research employed a qualitative case study design. Semi-structured interviews were conducted with nine purposively selected teachers, and data were analysed using thematic analysis. Findings reveal three critical themes: (1) Monolingual Guilt vs. Pragmatic Necessity, highlighting the internal tension of using home languages for cognitive scaffolding; (2) Affective Humanization, where translingual strategies are used to lower anxiety and build rapport; and (3) Strategic Compliance, where teachers perform monolingual identities during formal evaluations. The study concludes that translingualism is a sophisticated instructional competency rather than a pedagogical failure. It advocates for a shift toward context-sensitive language policies that formally recognise strategic scaffolding as a tool for educational equity and the preservation of indigenous linguistic identities.